JAMBI FOREST HONEY TO INHIBIT CARIOGENIC BACTERIUM STREPTOCOCCUS MUTANS: IN VITRO STUDIES - Mira Sri Gumilar; Karin Tika Fitria (Politeknik Kesehatan Kemenkes RI Jakarta I, 2023)
Background: The most important factor that causes caries is dental and oral hygiene. One attempt to maintain dental and oral hygiene is cleaning up plaque on teeth. Except of brushing teeth, many studies shown that gargling with honey could reduce dental plaque score. Method: The design of this study was an in vitro experimental design study with posttest control only design using disk diffusion technique. The Sample of this study was Streptococcus mutans culture bacterium. The sample of this study was divided into five groups, namely the control group, the treatment group with branded honey, the treatment group with branded mouthwash contain of 26,1% alcohol, the treatment group with branded mouthwash contain of 0,2% Chlorhexidine Gluconate, and the treatment group with acacia carpa honey. The data was obtained from the diameter of inhibit zone in Streptococcus mutans. Analysis was done to that data and carried out using the Kruskal Wallis and Mann Whitney tests. Result: The result showed that acacia carpa honey was more effective in inhibiting the growth of Streptococcus mutans bacteria compared to the control group, packaged honey, and brand mouthwash containing 21.6% alcohol. Conclusion: Acacia carpa as Jambi forest honey is effective in inhibiting the growth of Streptococcus mutans bacteria.